Digital Literacy, Academic Self-Efficacy, and Student Engagement: Its Impact on Student Academic Performance in Hybrid Learning - Fitra Jaya; Sucipto Sucipto (Journal of Innovation in Educational and Cultural Research, 2023)
Hybrid learning is a learning design approach that has been widely used by educational institutions by combining face-to-face learning components and technology-based learning pedagogy. In practice, hybrid learning demands to produce the same quality of academic achievement as face-to-face learning, so it requires special attention from lecturers to create meaningful learning experiences for students. This study specifically aims to analyze and evaluate academic performance in hybrid learning by exploring several factors, such as digital literacy, academic efficacy, and student engagement. This research was followed by 107 pre-service teacher students who participated in hybrid teaching spread across four different provincial regions. The data collection instrument used was a questionnaire, and academic achievement was measured through a Grade Point Average (GPA).Â Â  The data analysis used in this study was path analysis. The results of this study reveal that student involvement is an important factor that affects academic achievement. In addition, digital literacy and academic self-efficacy indirectly affect academic performance through increased active social-emotional involvement of students in synchronous and asynchronous learning designs.